Knowledge economy and the impact of autonomy on innovation in progressive companies - Nebb, Steinar (Informe GEPEC, 2014)
The main object is to discuss how the knowledge economy, as a concept and discipline, can open new possibilities for innovation around business development, strategy, management and leadership. Two questions are raised: 1. What is the innovative impact of knowledge economy on budgeting in companies? 2. What can we learn from co-workers’ experiences in the Norwegian oil company Statoil when it comes to autonomy in strategic goal setting and innovation? Teamwork and leadership based on principles in Beyond Budgeting appear to mitigate or eradicate some of the role conflicts between employer and employee. Statoil has introduced new principles of corporate management where the traditional budget is replaced with strategy focused policy documents prepared by the employees in team, supported by periodical economical prognoses. According to Statoil, by involving an entire organization in processes related to strategy and resource allocation, knowledge is applied innovatively.